2015
DOI: 10.5114/ms.2015.52912
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA as an essential component and therapeutic target of microbial biofilm

Abstract: The dominant part of human infections is associated with biofilm formations. Biofilm represents structured communities of bacterial or fungal cells enclosed in self-produced polymeric matrixes adherent to supporting surfaces. Microbial DNA and the host cell DNA, after their release at the infection site, show the ability to promote biofilm formation. Between the different constituents of biofilm matrixes, extracellular DNA (eDNA) may be the only component indispensable for the initial attachment and early biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Kaplan et al [91] observed 10-fold biofilm increase induced by subminimal inhibitory concentrations of β-lactam antibiotics added to a MSRA strains culture. They proved that it was dependent on cell lysis and in consequence the DNA released into the environment was utilized for the construction of matrix biofilm [92,93]. Taking into account our resultsthe growth curves of derivatives were not disturbed, so the increase of biofilm formation did not result from the increase of lysed bacterial cells.…”
Section: Amoxicillin Increases Biofilm Formationsupporting
confidence: 51%
“…Kaplan et al [91] observed 10-fold biofilm increase induced by subminimal inhibitory concentrations of β-lactam antibiotics added to a MSRA strains culture. They proved that it was dependent on cell lysis and in consequence the DNA released into the environment was utilized for the construction of matrix biofilm [92,93]. Taking into account our resultsthe growth curves of derivatives were not disturbed, so the increase of biofilm formation did not result from the increase of lysed bacterial cells.…”
Section: Amoxicillin Increases Biofilm Formationsupporting
confidence: 51%
“…By then, exDNA was found to be omnipresent, and with this awareness, a variety of research foci on different natural environments emerged:The persistence and ecological relevance of exDNA in soil (reviewed by Levy-Booth et al 2007; Pietramellara et al 2009);The persistence, function and turnover of exDNA in marine and aquatic ecosystems (reviewed by Torti et al 2015);The occurrence, relevance of exDNA and possible exDNA-derived therapies in the human body (reviewed by Aucamp et al 2016; Cooper et al 2013; Thierry et al 2016);The importance and the functions of exDNA in the formation of biofilms of pathogenic and environmental microorganisms (reviewed by Montanaro et al 2011 and Wnorowska et al 2015 (exDNA), Hobley et al 2015 (biofilms in general), Wolska et al 2016 (genetic control), Payne and Boles 2016 (matrix interactions and resulting implications) and Azeredo et al 2017 (methods)).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation usually exhibits resistance to classical antibiotic treatment, which is conditioned by an increase of total macromolecules contents of the biofilm matrix. 38,39 In effect, nanotechnologybased therapies may be promising in the eradication of bacterial and fungal pathogens, including those resistant to conventional antibiotic therapy. 19 In our study, the antimicrobial properties of magnetic nanoparticles functionalized by the well-known antiseptic, CHX, were thoroughly analyzed.…”
mentioning
confidence: 99%